Board independence and operating performance: analysis on (French) company and individual data. Issue 52 (7th November 2016) - Cavaco, Sandra; Challe, Edouard; Crifo, Patricia; Rebérioux, Antoine; Roudaut, Gwenaël
ABSTRACT: This article studies the relationship between board independence and firm operating performance in French listed companies. We take advantage of an original database, with a time-series dimension that can be used to mitigate heterogeneity and dynamic endogeneity issues. In addition, this database can be disaggregated at the individual (director) level. This design enables us to introduce firm fixed effects and individual fixed effects in firm performance equations, thereby controlling for heterogeneity at the firm and individual levels. Our main result is to document a significant negative relationship between independence and accounting performance. This result suggests that, in the French context, the costs of independence (i.e. the informational gap supported by independent directors compared to insiders and affiliated directors) outweigh the benefits of independence (i.e. the reduction in agency costs).